Rasio Kecukupan Pemenuhan Modal Minimum (KPPM) terhadap Eksposur Aktiva Tertimbang Menurut Resiko (ATMR) Bank Syariah - Maughfiroh, Suci (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2020)
The banking world is inseparable from the aspect of capital. In running a business, capital is needed. Capital is a driving factor of various sectors of activity. In order for banks to develop healthily and be able to compete in international banking, bank capital must always follow the applicable international standards, which are determined by Banking For Internasional Sattlement (BIS) i.e. (CAR) by 8%. The purpose of this study is to review or analyze the Minimum Capital Adequacy Ratio (KPPM) to the Risk Weighted Assets (ATMR) of BNI Syari'ah 2018. To find out the bank can meet its capital well or not with the risk constraints that may arise from the assets owned. The results showed that the BNI Syariah Capital Adequacy Ratio Percentage was 19.24% from the comparison of Capital and Reserves with Risk Weighted Assets (ATMR). In need of an increase in the Minimum Capital Adequacy Ratio (KPPM) in BNI Syariah banks so that the bank can fulfill all obligations or minimize losses from the risks that occur.